A general survey on the presence of decapitating fly (Genus:pseudacteon) attacking fire ant (Genus:solenopsis) in Samarahan Division, Sarawak - Panimalar, a/p Batumale (Universiti Malaysia Sarawak (UNIMAS), 2012)
Decapitating fly is a scuttle fly which is also known as phorid fly and Pseudacteon fly. The fly is a member of the family Phoridae in section Aschiza and genus Pseudacteon. The Pseudacteon species is a parasitoid of fire ant which lay or injects its eggs into the ant’s thorax. Larvae of the Pseudacteon fly lives and complete their metamorphosis inside the head of the ant, consuming the head contents and eventually kill the ant by decapitating the head with their enzyme. The Pseudacteon fly was studied by collecting the fire ants in Samarahan division. Fire ants belong to the order Hymenoptera. The genus of the fire ants studied is Solenopsis. Solenopsis was detected at Kpg. Sebayor, Kpg. Meranek and Tmn. Samarindah of Samarahan division. The Pseudacteon was not detected and may be concluded that it is also not in Samarahan division.